Management Of Boarding School Leaders Towards Teaching Tahfidz - Yuri, Jennifer; Crosbie, Kho; Joanna, Charvet (Journal Neosantara Hybrid Learning, 2023)
The running of the tahfidz program in schools is the authority of the school principal in realizing the sustainability of the program by school goals. This is also the management of the principal to teachers in teaching tahfidz. The purpose of this study was to find out how the management of the pesantren leadership towards teachers in teaching tahfidz at SDIT Masjid Raya Darat Batu. In this study, researchers used a qualitative descriptive method. The research subjects were school principals and tahfidz teachers at SDIT Masjid Raya Darat Batu. Data collection techniques through in-depth interviews in the form of conducting face-to-face interviews with school principals and tahfidz teachers who view the phenomenon under study. The results of the study explained that the SDIT of the Masjid Raya Darat Batu, the head of the school formed a religious position and appointed a special tahfidz teacher to educate students at school. The tahfidz program at school can run well, it is inseparable from how the principal's management and the teacher's strategy in teaching tahfidz in class.